Research and Development on Bio-products for Crop Production in China: A Short Communication - Song, J. J.; Soytong, K. (International Journal of Agricultural Technology, 2018)
The potential microorganism was isolated and screening to promote the growth for crop production in China. The isolates are screened for increasing plant growth and induce plant immunity. Bio-products are developed and tested in several kinds of plants eg. peach and citrus etc. Chaetomium sp. and Bacillus sp. were found and developed to be bioformulation for plant growth. Bio-products has developed as Bio-nutrient 1 (Chaetomium and Bacillus), Bio-nutrient 2 (liquid natural nutrient), Bio-nutrient 3 (natural substances for insect protection) and nano-kytex for plant immunity. Further research findings are still going on in progress.